PENGARUH PERSEPSI KEBERMANFAATAN DAN PERSEPSI KEMUDAHAN PENGGUNAAN TERHADAP MINAT PENGGUNAAN LAYANAN PEMBAYARAN DIGITAL GO-PAY - Tony Sitinjak, MM (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
One of the phenomena that occur in Indonesia in today’s digital economy era is that people began to implement a payment system that use electronic money. Therefore, the researcher sets out the formulation of the problem as follows: